The Role of Information and Communication Industry (ICT) in the Reduction of Greenhouse Gas Emissions in Canada - Bentolhoda Abdollahbeigi; Farhang Salehi (Universitas Prasetiya Mulya, 2020)
According to the concerted efforts to reduce global greenhouse gas emissions (GHGE), the Information and Communication Industry (ICT) has received little attention as a significant contributor to GHG. ICT has a very significant role to play in reducing greenhouse gas emissions in Canada. While climate challenges increase, there is a growing need to reduce Greenhouse gas emissions. The ICT sector has an important role in enabling significant reductions in those emissions and costs. This current study aims to examine the effects of GHGE on climate change in Canada with a focus on the ICT sector. This paper will provide a review of ICT definitions and Greenhouse gases and how GHGE can be reduced. This paper presents an approach to investigating the impact of information and communication technologies (ICTs) on Greenhouse gases emission and their effect on climate change in Canada.Keywords: ICT, Greenhouse gas emissions, Climate change, Canada* Research Department, APH Rosha Consulting Group Ltd., 18 dey street, No 65, Sary, Mazandaran, Iran https://doi.org/10.21632/irjbs.13.3.307-315